SANTA.Y - SEBUAH PASAR TRADISIONAL BARU - Amanda Ineza Gandasasmita; Fermanto Lianto (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2021)
The Covid-19 pandemic case, which until now has no solution, causes us to live in the new normal era. But this new normal era has not completely prevented the spread of Covid-19. Many areas are feared to become new clusters of deployment and one of them is traditional markets. For millions of people in Indonesia, traditional markets are on average the first place to shop for daily necessities, apart from being more affordable than supermarkets, there is an opportunity to bargain on prices. Since the outbreak of the Covid-19 case, the income of traders has decreased because people are afraid to shop at traditional markets for reasons that health and hygiene are not guaranteed. Many new policies in the new normal era have not helped to restore the economy of traders and are also exacerbated by a lack of public understanding Covid-19. Santa modern market is one of the thematic markets which is quite well known, but over time, Santa modern market is starting to be abandoned. Then it is also exacerbated by the influx of pandemic which causes economic losses to its traders. So, this project is trying to make a new face about traditional markets in Indonesia and also presents a solution for the traditional market of the future. With a green concept in buildings and implementing a cross-ventilation system to prevent the spread of Covid-19, this project goals is to “Santa modern market” able to dwell during a pandemic to the future. Keywords: Covid-19; Dwelling; New Normal; Traditional Market Abstrak Kasus pandemi Covid-19 yang sampai sekarang belum ada solusinya menyebabkan kita harus hidup di era new normal. Tetapi era ini belum sepenuhnya dapat mencegah penyebaran Covid-19. Banyak area yang dikhawatirkan akan menjadi cluster baru penyebaran dan salah satunya adalah pasar tradisional. Untuk jutaan orang di Indonesia, pasar tradisional rata-rata menjadi tempat pertama untuk berbelanja kebutuhan sehari-hari, selain karena harganya yang lebih terjangkau dibanding pasar swalayan, ada keesmpatan untuk tawar menawar harga. Semenjak maraknya kasus Covid-19, pendapatan pedagang menurun karena masyarakat takut untuk berbelanja ke pasar tradisional dengan alasan kesehatan dan kebersihan yang belum terjamin. Banyak kebijakan baru di era new normal yang ternyata tidak membantu untuk mengembalikan ekonomi para pedagang dan juga diperparah dengan kurangnya pemahaman masyarakat tentang bahaya Covid-19. Pasar Santa merupakan salah satu pasar tematik yang cukup terkenal tetapi seiring berjalannya waktu, pasar Santa mulai ditinggalkan. Kemudian hal ini juga diperparah dengan masuknya pandemi yang menyebabkan kerugian ekonomi para pedagangnya. Sehingga proyek ini berusaha untuk membuat suatu wajah baru tentang pasar tradisional di Indonesia dan juga menghadirkan suatu solusi untuk pasar tradisional di masa depan. Dengan konsep hijau di dalam bangunan dan menerapkan sistem cross-ventilation untuk mencegah penyebaran Covid-19 bertujuan untuk menjadikan pasar Santa untuk dapat ber-dwelling di tengah pandemi hingga masa depan.